JC polyomavirus infection is strongly controlled by human leucocyte antigen class II variants. - Emilie Sundqvist (Public Library of Science (PLoS), 2014)
JC polyomavirus (JCV) carriers with a compromised immune system, such as in HIV, or subjects on immune-modulating therapies, such as anti VLA-4 therapy may develop progressive multifocal leukoencephalopathy (PML) which is a lytic infection of oligodendrocytes in the brain. Serum antibodies to JCV mark infection occur only in 50-60% of infected individuals, and high JCV-antibody titers seem to increase the risk of developing PML. We here investigated the role of human leukocyte antigen (HLA), instrumental in immune defense in JCV antibody response. Anti-JCV antibody status, as a surrogate for JCV infection, were compared to HLA class I and II alleles in 1621 Scandinavian persons with MS and 1064 population-based Swedish controls and associations were replicated in 718 German persons with MS. HLA-alleles were determined by SNP imputation, sequence specific (SSP) kits and a reverse PCR sequence-specific oligonucleotide (PCR-SSO) method. An initial GWAS screen displayed a strong HLA class II region signal. The HLA-DRB1*15 haplotype was strongly negatively associated to JCV sero-status in Scandinavian MS cases (OR = 0.42, p = 7×10(-15)) and controls (OR = 0.53, p = 2×10(-5)). In contrast, the DQB1*06:03 haplotype was positively associated with JCV sero-status, in Scandinavian MS cases (OR = 1.63, p = 0.006), and controls (OR = 2.69, p = 1×10(-5)). The German dataset confirmed these findings (OR = 0.54, p = 1×10(-4) and OR = 1.58, p = 0.03 respectively for these haplotypes). HLA class II restricted immune responses, and hence CD4+ T cell immunity is pivotal for JCV infection control. Alleles within the HLA-DR1*15 haplotype are associated with a protective effect on JCV infection. Alleles within the DQB1*06:03 haplotype show an opposite association. These associations between JC virus antibody response and human leucocyte antigens supports the notion that CD4+ T cells are crucial in the immune defence to JCV and lays the ground for risk stratification for PML and development of therapy and prevention.